Double-lumen endotracheal tube in pediatric intensive care unit: A lifesaver in a leukemic child with pulmonary hemorrhage: A case report - Parvathy S Menon; Indira Jayakumar; R Vikram Rajkumar; Venkateswaran Vellaichamy Swaminathan; C Vasantha Roopan (Wolters Kluwer Medknow Publications, 2023)
We describe a case of life-threatening pulmonary hemorrhage in a boy with leukemia. He had episodes of massive hemoptysis for which he was intubated and resuscitated with multiple blood products, hemostatic measures (tranexamic acid and recombinant factor VIIa), and inotropes. Chest X-ray revealed left upper lobe homogeneous opacity. Within 12 h, in view of persistent massive pulmonary bleed and hypoxia, he was reintubated with a left-sided double-lumen endotracheal tube (DLT). Following reintubation with DLT, pulmonary bleed could be managed. He was treated for probable left upper lobe angioinvasive aspergillosis. He was weaned off ventilatory support and extubated after 48 h to high flow nasal canula (HFNC). This case is to highlight the importance of early use of DLTs in pulmonary hemorrhage due to suspected unilateral lung pathologies to facilitate isolation of diseased lung, improve ventilation, and prevent spillage of blood to the contralateral normal lung. It serves as a temporizing measure, while aggressive efforts to identify and control the bleed are underway.